From the Arctic to the tropics: multibiome prediction of leaf mass per area using leaf reflectance. Issue 4 (17th September 2019) - Serbin, Shawn P.; Wu, Jin; Ely, Kim S.; Kruger, Eric L.; Townsend, Philip A.; Meng, Ran; Wolfe, Brett T.; Chlus, Adam; Wang, Zhihui; Rogers, Alistair
Summary: Leaf mass per area (LMA) is a key plant trait, reflecting tradeoffs between leaf photosynthetic function, longevity, and structural investment. Capturing spatial and temporal variability in LMA has been a long‐standing goal of ecological research and is an essential component for advancing Earth system models. Despite the substantial variation in LMA within and across Earth's biomes, an efficient, globally generalizable approach to predict LMA is still lacking. We explored the capacity to predict LMA from leaf spectra across much of the global LMA trait space, with values ranging from 17 to 393 g m −2 . Our dataset contained leaves from a wide range of biomes from the high Arctic to the tropics, included broad‐ and needleleaf species, and upper‐ and lower‐canopy (i.e. sun and shade) growth environments. Here we demonstrate the capacity to rapidly estimate LMA using only spectral measurements across a wide range of species, leaf age and canopy position from diverse biomes. Our model captures LMA variability with high accuracy and low error ( R 2  = 0.89; root mean square error (RMSE) = 15.45 g m −2 ). Our finding highlights the fact that the leaf economics spectrum is mirrored by the leaf optical spectrum, paving the way for this technology to predict the diversity of LMA in ecosystems across global biomes.